Empowering women with social tecnologies: the transformation of menstrual hygiene through production of reusable pad (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The article analyzes the impact of reusable sanitary pad production workshops on vulnerable communities, highlighting the promotion of sustainability, female empowerment and gender equality. Through access to safe products, income generation and environmental awareness, social technologies empower women, reduce waste and demystify menstrual taboos, showing positive results in the short term. However, gaps such as long-term evaluation and the inclusion of different perspectives were identified, suggesting the need for additional research to gain a more comprehensive and in-depth understanding of the impact of these initiatives.
Keywords: sustainability; empowerment; social technologies